2022
DOI: 10.3390/ijms23073970
|View full text |Cite
|
Sign up to set email alerts
|

Pain Modulation from the Locus Coeruleus in a Model of Hydrocephalus: Searching for Oxidative Stress-Induced Noradrenergic Neuroprotection

Abstract: Pain transmission at the spinal cord is modulated by noradrenaline (NA)-mediated actions that arise from supraspinal areas. We studied the locus coeruleus (LC) to evaluate the expression of the cathecolamine-synthetizing enzyme tyrosine hydroxylase (TH) and search for local oxidative stress and possible consequences in descending pain modulation in a model of hydrocephalus, a disease characterized by enlargement of the cerebral ventricular system usually due to the obstruction of cerebrospinal fluid flow. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 62 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…Descending noradrenaline projections that innervate the lumbosacral segments of the spinal cord are required for the coordination of bladder contractions and EUS relaxation during voiding [15,38]. We previously showed that the PAG is strongly affected by the dilation of the cerebral ventricles in the hydrocephalus model used in the present study [21]. Here, the PAG was analyzed to evaluate the expression of the c-Fos protooncogene, as this is an indicator of neuronal activity [39].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Descending noradrenaline projections that innervate the lumbosacral segments of the spinal cord are required for the coordination of bladder contractions and EUS relaxation during voiding [15,38]. We previously showed that the PAG is strongly affected by the dilation of the cerebral ventricles in the hydrocephalus model used in the present study [21]. Here, the PAG was analyzed to evaluate the expression of the c-Fos protooncogene, as this is an indicator of neuronal activity [39].…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, these animals also showed increased levels of DBH, the enzyme involved in the synthesis of noradrenaline, at the Onuf's nucleus, where the motoneurons that regulate bladder contraction are located. We previously reported an increase in noradrenergic innervation in hydrocephalic animals at the LC [21]. The spinal noradrenergic system has a modulatory role in the control of the micturition reflex, and it is likely that an association between altered micturition and changes in noradrenergic innervation at the Onuf´s nucleus occurs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations